Advancing Tennis Analytics: Comprehensive Modeling for Momentum Identification and Strategic Insights - Lin, Junhai; Shao, Pengjin; Zhang, Qingyang (International Journal of Computer Science and Information Technology, 2024)
The 2023 Wimbledon men's singles final featured a thrilling clash between the emerging Spanish talent Carlos Alcaraz and the seasoned Novak Djokovic. Djokovic initially exerted control over the game, but Alcaraz effectively turned the tables and emerged victorious, highlighting the significance of "momentum" in the sport. Despite frequent discussion, effectively quantifying and forecasting the impact of this phenomenon poses significant challenges. Question 1 investigates the methods of tracking the progress of a tennis match and identifying players who demonstrate exceptional performance at specific moments. We constructed a model that considers variables such as serve probability advantage, technical indications, physical fitness, and mental condition. The model use time series analysis to monitor the dynamics of the game. It presents the game progress and player performance through interactive charts, allowing for efficient tracking of shifts in game momentum. Question 2 examines the influence of "momentum" on the game's result. We employed the XGBoost machine learning technique to construct a model, coupled with the particle swarm optimization algorithm to fine-tune parameters, and examined the pivotal aspects that influence the game's momentum. The model's findings demonstrate a notable association between momentum and game performance, which contradicts the belief held by certain coaches that game flow is purely impacted by random events. Question three necessitates the anticipation of significant moments of change in momentum within the game. We developed a predictive model that uses the PSO-XGBoost forest algorithm to accurately forecast the timing of momentum transitions. This is achieved by identifying and analyzing important statistics. The findings demonstrate that the model has the capability to precisely anticipate moments of momentum change, hence offering strategic guidance for coaches and players. Question 4 assessed the adaptability of the model in various competitive settings and produced a suggestion report based on the study of the model's results. We examine the implementation of the concept in several game scenarios and offer coaches and athletes strategic counsel to enhance their readiness and reaction to pivotal occurrences throughout the game. In conclusion, our research offers a comprehensive viewpoint on the significance of momentum in tennis matches and demonstrates the potential of machine learning methods in forecasting and capitalizing on this phenomena. Our approach not only improves comprehension of match progression, but also offers direction on how to implement these observations in actual matches.